2001
DOI: 10.1097/00002480-200111000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Preserving Central Blood Volume: Changes in Body Fluid Compartments During Hemodialysis

Abstract: The understanding of fluid changes during hemodialysis (HD is essential for reducing complications as well as efficacy of the procedure. Bioimpedance spectroscopy provides a non invasive method of measuring total body water (TBW), the distribution of intra (ICF) and extracellular (ECF) fluids, and their changes during HD. Segmental bioimpedance may be used to measure the same fluid shifts but from different body segments; the technique has previously been shown to com pare well with whole body measures. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 13 publications
4
42
2
Order By: Relevance
“…Bioimpedance analysis has been used as a tool for body composition/body fat analysis [4][5][6][7][8][9] and in the assessment of fluid imbalance in hemodialysis patients [10][11][12][13]. It has not yet been applied to the prosthetics field.…”
Section: Electrical Bioimpedancementioning
confidence: 99%
See 1 more Smart Citation
“…Bioimpedance analysis has been used as a tool for body composition/body fat analysis [4][5][6][7][8][9] and in the assessment of fluid imbalance in hemodialysis patients [10][11][12][13]. It has not yet been applied to the prosthetics field.…”
Section: Electrical Bioimpedancementioning
confidence: 99%
“…Segmental bioimpedance analysis has been used successfully to determine changes in V ECF with respect to body position [12,[22][23]. R ECF increased and V ECF decreased in the legs when subjects changed body position from sitting to supine to supine with elevated legs, indicating that fluid was redistributed from the legs into the trunk during supine positioning and leg elevation [22].…”
Section: (1)mentioning
confidence: 99%
“…5 During dialysis, plasma refilling is more dynamic from the leg in comparison with the trunk or arms, suggesting that the calf could be used as a window to monitor intradialytic changes in whole-body extracellular fluid volume. 6 The use of a higher dialysate sodium concentration (Ͼ140 mEq/L) is an effective means to ensure adequate vascular refilling and has proved to be among the most efficacious and best tolerated therapies for episodic hypotension. Sodium modeling is a technique in which the dialysate sodium concentration is varied during the course of the procedure.…”
mentioning
confidence: 99%
“…One of the goals is to improve predictive equations and to identify the effect of different parameters on the measures obtained [19,20]. In dialysis for example, it has been shown that fluid is removed predominantly from the extracellular and peripheral (arms, legs) compartments [21]. Thus, different biofluid models have been proposed to describe the whole body or individual organs.…”
Section: Usefulness Of Bioimpedance For the Kidney Disease Patientmentioning
confidence: 99%